Arahan Pengembangan Kawasan Strategis Minapolitan - Desti Rahayu Lataena; Mukti Ali; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2019)
The purpose of this plan is to know the potential and problems that can support the development of the minapolitan area, recommending the direction of the development of the zoning zone of the minapolitan area and the direction of developing the infrastructure of the minapolitan area. Data collection techniques carried out in the form of interviews, agency studies, and direct observation in the field. The analytical method used is the method of LQ (Location Quotient), supply chain analysis, linkert scale analysis, level of service analysis, and scalogram analysis. The results of the analysis of the potential of the Minapolitan area are obtained, namely the LQ value of superior capture fisheries namely anchovy and Cakalang fish. The aquaculture which is the main commodity is R.L Gracillaria. Based on the results of the linkert scale analysis of the availability of facilities in the Minapolitan area of ​​Malili sub-district by 75.7%. The results of the scalogram analysis based on the centralized index obtained by service hierarchy I are located in Wewangriu Village, Hierarchy II is located in Lakawali Village, Hierarchy III is located in Atue Village, Hierarchy IV in Balantang Village, Puncak Indah Village, Manurung Village, Tarabbi Village, Harapan Village, Desa Desa Baruga, Pongkeru Village, Ussu Village, and Malili Village. The recommendation for zoning directions for the minapolitan area is divided into 4 zones, namely: 1) the core zone of Minapolis in Wewangriu Village; 2) capture zone of Lakawali Pantai village center; 3) development zone in Atue Village; and 4) the linked zone in Balantang Village, Puncak Indah, Manurung, Tarabbi, Harapan, Baruga, Pongkeru, Ussu, and Malili Village.